Model Konsumsi Yang Bertanggungjawab Perspektif Alquran dan Hadis - Ferdi Dermawan Nasution; Rahmi Syahriza (Invention: Journal Research and Education Studies, 2026)
The current consumption model of Muslim society has transformed from mere regulatory compliance to a complex ethical lifestyle, marked by the phenomenon of "Patriotic Consumption" post-geopolitical issues that strengthen preferences for local products and the dominance of Gen-Z who rely more on digital visual validation and sustainability values. This type of research is a literature review, namely data collection with materials available in the library. The approach taken by researchers to analyze the meaning of responsible consumption in the Qur'an and hadith is a thematic interpretation approach. And this research uses Content Analysis which is used as a validation instrument to prove that the concept of responsible consumption according to the Qur'an and Hadith that after we as economic actors optimize all the resources around us (in the verses explained in the contents of the writings of livestock, mountains, plantation land, oceans with their riches, remember again the view of the Qur'an about property which is called Fadlum minallah) as a medium for life in this world, then we are directed to do good to our brothers, the poor, relatives in a good way without being stingy and wasteful. With the principles of consumption, the consumption pattern of a person and also society, is directed to the needs and obligations that are commensurate with the simplest possible life pattern according to the word of Allah SWT and Hadith.